2018
DOI: 10.1007/s00330-018-5707-5
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-high-field arterial spin labelling MRI for non-contrast assessment of cortical lesion perfusion in multiple sclerosis

Abstract: ObjectivesTo assess the feasibility of using an optimised ultra-high-field high-spatial-resolution low-distortion arterial spin labelling (ASL) MRI acquisition to measure focal haemodynamic pathology in cortical lesions (CLs) in multiple sclerosis (MS).MethodsTwelve MS patients (eight female, mean age 50 years; range 35–64 years) gave informed consent and were scanned on a 7 Tesla Philips Achieva scanner. Perfusion data were collected at multiple post-labelling delay times using a single-slice flow-sensitive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Eight articles were included in the field strength comparison (one post-mortem , seven in vivo ), eight publications in the sequence comparison (three post-mortem , five in vivo ) and five articles that validated UHF MRI data against histology. An overview of all included studies and relevant study parameters is provided in Appendix A , Bluestein et al, 2012a , Cohen-Adad et al, 2011 , Dury et al, 2019 , Fan et al, 2015 , Gaitan et al, 2013 , Herranz et al, 2020 , Jonkman et al, 2016a , Jonkman et al, 2016b , Kangarlu et al, 2007 , Kolber et al, 2017 , Kollia et al, 2009 , Metcalf et al, 2010 , Mistry et al, 2014 . Among the 25 in vivo studies, sample size ranged from 8 to 90 patients, mean age from 36 to 54 years and female proportion from 33 to 81%.…”
Section: Resultsmentioning
confidence: 99%
“…Eight articles were included in the field strength comparison (one post-mortem , seven in vivo ), eight publications in the sequence comparison (three post-mortem , five in vivo ) and five articles that validated UHF MRI data against histology. An overview of all included studies and relevant study parameters is provided in Appendix A , Bluestein et al, 2012a , Cohen-Adad et al, 2011 , Dury et al, 2019 , Fan et al, 2015 , Gaitan et al, 2013 , Herranz et al, 2020 , Jonkman et al, 2016a , Jonkman et al, 2016b , Kangarlu et al, 2007 , Kolber et al, 2017 , Kollia et al, 2009 , Metcalf et al, 2010 , Mistry et al, 2014 . Among the 25 in vivo studies, sample size ranged from 8 to 90 patients, mean age from 36 to 54 years and female proportion from 33 to 81%.…”
Section: Resultsmentioning
confidence: 99%
“…Recent clinical trials, neuropathological investigations and MRI imaging studies have drawn growing attention to the relevance of gray matter (GM) lesions and particularly cortical lesions (CL) in Multiple Sclerosis (MS) patients (13). In contrast to earlier assumptions (4, 5), recent studies reported that neuroinflammation is present in CLs, suggesting that active immune mechanisms and focal demyelination are present inside the cortical layer (68).…”
Section: Introductionmentioning
confidence: 99%